Parable and Realism in Capital Theory: The Surrogate Production Function - Samuelson, Paul A. (Review of Economic Studies, 1962)
Parable and Realism in Capital Theory: The Surrogate Production Function Get access Paul A. Samuelson Paul A. Samuelson Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 3, June 1962, Pages 193–206, https://doi.org/10.2307/2295954 Published: 01 June 1962